PESAN SEMIOTIK PADA TRADISI MAKAN TABHEG DI PONDOK PESANTREN - Bambang Subahri (Institut Agama Islam Syarifuddin Lumajang, 2020)
Tabheg is one type of food wrapped in banana leaves filled with rice with very simple side dishes such as salted fish, eggplant, chili sauce and crackers as a complement. Tabheg is a souvenir brought by the guardians of students when visiting their children in the boarding school. The tradition of bringing this tabheg is often found in Islamic boarding schools in the East Java, area Tapal Kuda. The tradition of eating tabheg for santri is a sign (representamen) with the values of togetherness and simplicity (interpretant) that can be conveyed through the form of food (object) that is shared by the students without distinguishing economic background and social stratification of the family. Phenomenon in the tradition of eating tabheg is believed to have a rich meaning of symbolic messages which are full of philosophical meanings so as to form patterns of human behavior. Exposure analysis of the tradition of eating tabheg is a qualitative study with a literature study approach, departing from the perspective of communication science using the concept of Charles Sanders Pierce with his trichotomies and psychological studies that form the basis of behavior formation. In addition it also aims to explore the constructive meaning of the pesantren tradition which is a reference to the santri mindset to shape behavior. The results of the analysis based on semiotic messages on the tabheg eating tradition for students based on representamen, interpretants and objects produce a constructive concept of santri personality characterized by traditional Islam. Where the santri character is built from the meaning implied in symbolic messages in the form of togetherness and simplicity that is internalized in the form of peace-loving behavior as a pesantren modality in realizing world peace.